MODEL OF CORPORATE GOVERNANCE OF A MODERN ENTERPRISE IN THE 21ST CENTURY - Siljanovska, Zorica (Journal of process management and new technologies, 2017)
Efficient and quality system of corporate governance built on high set international standards and principles allows setting goals that are consistent with the interests of all stakeholders. The definition of corporate governance made by the OECD, which today is one of the most widely accepted and comprehensive definition confirms the importance of all constituents and care for their interests when setting objectives. Quality corporate governance known mechanisms that establish a balance between the different interests of stakeholders. Each constituency is part of the mosaic should not be marginalized and ignored.